Divine Images, (Re) existences and Care in Times of Pandemic when Celebrating Espírito Santo in São Luís-Maranhão (Revista Internacional de Folkcomunicação, 2023)
The text proposes to reflect on some cosmovisions and imagery cosmoperceptions of peoples of African origin in São Luís-Maranhão regarding the cruel pandemic context of Covid-19 faced in the years 2020-2021, highlighting its impacts, in addition to its forms policies of (re)existences, focusing on the feast of the Divine Holy Spirit, the 'Divino do/ no Reviver', organized by Yalorixá Bianca Lopes in the Historic Center of the Ludovicense capital. As a methodology, we will move from a postcolonial/structuralist perspective to decolonial thinking (KRENAK, 2020). Among the investigative instruments, we highlight the value of anthropological field research. The problem pointed out - what are the senses and meanings of the festive interdiction images in the pandemic?! The results demonstrate the 'divine pandemic disobedience' as an element of continuity of doing ritual.
Keywords: Divine of Reviver; Parties; Covid-19